Increasing Creative Thinking of Students by Learning Organization with STEAM Education - Ahmad, D. N.; Astriani, M. M.; Alfahnum, M.; Setyowati, L. (Jurnal Pendidikan IPA Indonesia, 2021)
The purpose of this research is to analyze the changes in learning between learning before using the STEAM method and learning after using the STEAM method. Where the researchers analyzed the process of student activities in learning, namely in the course of making learning media to determine the ability of students to think creatively in developing the students' knowledge. In obtaining research data, researchers used an assessment score reference instrument, where the final product assessment was assessed by subject lecturers, learning media expert lecturers, and linguistics (language) lecturers. To find out whether there is a change in the ability to think creatively in each learning process before and after learning, the researcher uses a hypothesis test using the t-test. To find out whether there is a change in ability positively, namely the ability to think creatively in each learning process before and after learning, the researcher uses a hypothesis test using the t-test to find out this. It can be seen from the increase in the average learning outcomes before and after with an increase in the difference of 2.26 from the average before using the STEAM method in learning, which is 78.26. The results of the analysis test explain that the learning method using STEAM in learning has a positive impact on learning where students experience a significant average increase before and after being given learning using the STEAM method by providing hands-on experience through the project work process.